(untitled) (American Journal of Islam and Society, 2012)
These three books cover the common themes of the last century and a half of Muslim activism ‒ reform, radicalism, and the role of Islam in modern societies. Each book covers a different phase in the history of Islamic revivals and their interactions with modernity. John Calvert’s book is a study of Sayyid Qutb’s work during the phase of the heightened Cold War ideological contestations in the postcolonial period, both in the Muslim lands as well as globally. Kai Hafez’s book focuses largely on the last several decades when the study of democracy and democratization came to the forefront of the academic/policy scene in the West ‒ but also among the Muslim activists. Finally, John Esposito’s book spotlights the Muslim present and its possible futures. Combined, the books provide an overview of the important issues surrounding Muslim activism and possibilities for political and religious reform among the Muslims ...